Attenuation of morphine tolerance and dependence by thymoquinone in mice - Hossein Hosseinzadeh; Siavash Parvardeh; Alireza Masoudi; Mahsa Moghimi; Fatemeh Mahboobifard (Mashhad University of Medical Sciences, 2016)
Objectives: Dependence and tolerance are major restricting factors in the clinical use of opioid analgesics. In the present study, the effects of thymoquinone, the major constituent of Nigella sativa seeds, on morphine dependence and tolerance were investigated in mice. Materials and Methods: Male adult NMRI mice were made tolerant and dependent by repeated injections of morphine (50, 50, and 75 mg/kg, i.p. on 9 a.m., 1 p.m., and 5 p.m., respectively) during a 3-day administration schedule. The hot-plate test was used to assess tolerance to the analgesic effects of morphine. Naloxone (2 mg/kg, i.p.) was injected to precipitate withdrawal syndrome in order to assess the morphine dependence. To evaluate the effects of thymoquinone on tolerance and dependence to morphine, different single or repeated doses of thymoquinone were administered in mice. Rotarod was used to assess the motor coordination. Results: Administration of single or repeated doses of thymoquinone (20 and 40 mg/kg, i.p.) significantly decreased the number of jumps in morphine dependent animals. Repeated administration of thymoquinone (20 and 40 mg/kg, for 3 days) and also single injection of thymoquinone (40 mg/kg, on the fourth day) attenuated tolerance to the analgesic effect of morphine. None of the thymoquinone doses (10, 20, and 40 mg/kg) produced any antinociceptive effects on their own. Motor coordination of animals was impaired by the high dose of thymoquinone (40 mg/kg). Conclusion: Based on these results, it can be concluded that thymoquinone prevents the development of tolerance and dependence to morphine.